Fatigue damage of closed-cell aluminum alloy foam: Modeling and mechanisms. (June 2016) - Zhao, Modi; Fan, Xueling; Wang, T.J.
Highlights: We experimentally study the damage mechanisms of closed-cell Al alloy foam. Four major categories of fatigue damage mechanism are concluded. A statistical fatigue damage model is developed for foam material. Abstract: The objective of this work is to experimentally investigate the damage evolution and damage mechanism in closed-cell aluminum alloy foam under tension–tension fatigue loading. Constant amplitude fatigue tests are performed for the aluminum alloy foam, and experimental results indicate the large scatter of the fatigue damage in the aluminum alloy foam. To describe the fatigue damage with large scatter, a statistical fatigue damage model is developed on the basis of continuum damage mechanics. It is seen that the statistical damage model can describe the fatigue damage of the foam. Scanning electron microscopy (SEM) observation on the fracture surface of the tested specimen is carried out to understand the damage mechanisms of the foam. Four major categories of fatigue damage mechanism are concluded, i.e. damage initiates from the material surface, damage initiates on the cell wall, damage initiates at the intersection of several cell walls and damage initiates from the edge of cell. The high-resolution SEM images reveal that the fatigue mechanisms of the foam are mainly governed by the cell structure.